EP175/#1112 Comparison of U.S. and Zambian OB/GYN residency training programs. (4th December 2022) - Hicks, Michael; Hicks, Maya; Chanda, Kenneth; Mwanahamuntu, Mulindi; Jones, Monica; Mattison, Anissa; Parham, Groesbeck
Abstract : Objectives: In order to explore perceived inequities in post-graduate medical education between high and low income countries, we evaluated the average minimal procedural requirements between a U.S. and Zambian Ob/Gyn residency programs. Methods: Each respective program's metrics related to their minimum procedural requirements were recorded, and included the following indicators: vaginal deliveries; C-sections; abdominal hysterectomies; laparoscopic hysterectomies; laparoscopic procedures; hysteroscopies; cancer cases; vaginal hysterectomies; abortions; obstetrical ultrasounds; cystoscopies; incontinence and pelvic floor surgery. We also included the presence or absence of an official ultrasound rotation; time on obstetrics and gynecologic clinical services exclusively; the presence or absence of protected didactic time; subspecialty and off service rotations. A comparison was made related to these various categories and the average procedural numbers at each level to determine differences in trends and degree of exposure to surgical procedures during training. Results: Minimal procedural requirements were met by both the U.S. and Zambian programs. The Zambian program had higher minimal standards for open surgical cases and the U.S. program had higher minimal standards for procedures that were associated with high end technology such as ultrasound and minimally invasive surgery. ( table 1 and 2 ). Conclusions: There were no significant differences in the Zambian and U.S. Ob/Gyn post-graduate training programs relative to their respective metrics. A more extensive analysis is required to determine the actual competency levels that are produced by the respective training systems.